Assessment of prognostic markers of alopecia areata in pediatric patients - Nayak, Jhini; Bhatia, Kailash; Namdeo, Chaitanya (International Journal of Research in Dermatology, 2023)
Alopecia areata (AA) is associated with impairment of psychological health being more pronounced in pediatric population. Hence, it becomes imperative to study the AA in pediatric population so that early diagnosis and adequate treatment can be initiated at early stage to prevent further morbidity associated with the condition. This observational study was conducted in the department of dermatology venereology and leprosy, SAIMS and PG institute, Indore, India after obtaining approval from the IEC. The study included 14 children with AA who visited the hospital over the period of 1 year. Results showed that Mean age of the patients was 8.8±3.423 years with M:F ratio of 3:4. AA subtotalis was found to be most frequent (57.1%). The mean duration of alopecia was reported to be 9.3±7.965 months. The most common finding was the presence of a single patch (35.7%) and 50% of subjects have had a single episode of the disease. 64.3% of children had involvement of multiple sites with scalp being the most common (85.7%). There is high prevalence of markers of disease severity and activity amongst pediatric patients with AA. High prevalence of nail changes, mark hair (64.3%), coudability hair (50.0%), yellow dots (42.8.0%), black dots (78.6%), S. vellus hair (28.6%) shows that children have high chance of AA progressing to severe forms. There is high prevalence of markers of disease severity and activity amongst pediatric patients with AA with AA subtotalis more common among children as compared to the patchy type.